CORELATION OF THE COLOR OF THE STRAW FUEL PELLETS TO THE COMPRESSIVE PROPERTIES - Kubik, Lubomir (Journal on Processing and Energy in Agriculture, 2021)
The aim of the manuscript was the evaluation of the compressive properties of the straw pellets in the relation to the color differences between them. Modulus of elasticity and failure strength of the pellets at the compression were determined. A testing machine Andilog Stentor 1000 (Andilog Technologies, Vitrolles, France) was employed for uniaxial compression tests. L*, a*, b* color coordinates of CIE LAB 3D color space were used to the characterization of pellet’s color. Two sorts of pellets were measured: made from wheat straw and made from the mixed wheat and barley straw. Samples were measured by a spectrofotometer 3NH YS3020 and computed as the mean of twenty samples. The correlation of the pellet color with the mechanical properties, mainly modulus of elasticity and failure strength of the pellets at the compression were realized to obtain relation of the deformation process to the pellet’s color of different sorts of pellets.